Study guides

☆☆

Q: What is 4n plus 1 times 2n plus 6?

Write your answer...

Submit

Still have questions?

Related questions

12+4n = 2n12+4n-4n = 2n-4n12 = -2n-1/2(12 = -2n)-6 = n

If the given equation were factorized it would be: 2n2 + 4n = 2n(n+1) Another Answer:- The given expression when factored is 2n(n+2)

n(2n - 1)(2n + 7)

If you mean: 4n = 1-23-2n then 6n = -22 and so n = 11/3

7n -1n,0n,1n,2n,3n,4n,5n,6n,7n 1 2 3 4 5 6 7 8 9

Any even number can be written in the form 2n for some natural number n.Any odd number can be written as 2n+1 for a natural number nNow add an even to an odd.2n+2n+1=4n+1 which is 2(2n)+1 and this is the form for an odd number.

It is an expression that can be simplified to -4n-1

4n+13=1 -13 -134n=-12/4 /4n=-3

The question can be represented as the equation, 2n + 5 = 4n + 3 where n is the unknown number. 2n + 5 = 4n + 3 : subtract 2n from both sides 5 = 2n + 3 : subtract 3 from both sides 2 = 2n : divide both sides by 2 1 = n The unknown number has been identified as 1.

FOIL deals with polynumerals in math. An example is a difference of squares as in (2n - 2)2 or (2n + 2)(2n - 2) =F stand for first--2n X 2n = 4n2O stands for outside-- 2n X -2 = -4nI stands for inside-- -2 X 2n = 4nL stands for last--2 X -2 = -4In the end you get:4n2 - 4n + 4n - 4 = 4n2 - 4Can you see how everything is squared and the two numbers are being subtracted?

That factors to (2n + 1)(n + 2)

The sum of 2n, for n= 0 to 29.

1

When n=53, then 2n + 1 = 107

6=(1-2n)+5 6-5=(1-2n)+5-5 1=1-2n 1-1=1-1-2n 0=-2n 0/-2=-2n/-2 0=n

5n + 1 = 10 + 2n5n - 2n + 1 - 1 = 10 - 1 + 2n - 2n3n = 93n/3 = 9/3n = 3

n = 1 7n + 6n - 5 = 4n + 4 13n - 5 = 4n + 4 13n - 4n - 5 = 4n - 4n + 4 9n - 5 = 4 9n -5 + 5 = 4 + 5 9n = 9 n = 1

(n2 + 2n - 1) (n2 + 2n - 1) = n4 + 2n3 - n2 + 2n3 + 4n2 - 2n - n2 - 2n + 1 = n4 + 4n3 + 2n2 - 4n + 1 try with n = 5: (5 squared + 10 - 1) squared = 34 squared = 1156 with formula (5^4) + (4 *(5^3)) + (2 * (5^2)) - (4 * 5) + 1 = 625 + 500 + 50 - 20 + 1 = 1156

Yes. Let the two consecutive odd numbers be (2n - 1) and (2n + 1) for all values of integer n (ie n ∈ ℤ) Then their sum is: sum = (2n - 1) + (2n + 1) = 2n + 2n = (2 + 2)n = 4n = a multiple of 4, so is divisible by 4.

I am assuming that 2n is an algebraic expression, and n is limited to positive integer values. The first 4 multiples of 2n are 0 (2n*0), 2n (2n*1), 4n (2n*2), and 6n (2n*3). If you are looking for non-0 multiples, you would also include 8n (2n*4).

aneuploidy

The sum of the numbers given is 31. 1 + 2 + 4 + 8 + ... + 2n = 2n+1 - 1

1/2n + 1/(2n+2) = 1/2*[(1/n + 1/(n+1)] = 1/2*(2n+1)/[n*(n+1)] or (2n+1)/[2*n*(n+1)]

They are 1, 2, 4, m, 2m, 4m, n, 2n, 4n, mn, 2mn and 4mn.

use mathematicl induction to show that (5/4/4n+1)powerox1/2< or equal(1.3.5....(2n+1)/2.4.6.....(2n)< or equal(3/4/2n+1)power of 1/2